2023
DOI: 10.3390/bioengineering10030286
|View full text |Cite
|
Sign up to set email alerts
|

Smoothness of Gait in Overweight (But Not Obese) Children Aged 6–10

Abstract: Excessive body mass represents a serious threat to the optimal psychophysical development of children, and it is known to be able to significantly affect their locomotor capabilities, making them more prone to the development of musculoskeletal disorders. However, despite the relevant number of existing studies, a clear gait pattern of overweight children has not been defined yet, particularly in the case of a mass excess that is relatively small (i.e., in those not obese). In the present study, we employed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Costeffective and easy to set up, they can provide useful settings for occupational therapy (Corrêa et al, 2013;Pruszyńska et al, 2022;Tada et al, 2022). An example is the immersive virtual kitchen game proposed by Pau et al (2023a) where the environment provides several activities of daily living tasks (e.g., tidying up, cooking, washing the dishes, etc.). Questionnaires conducted on an 8-week study on PwMS showed overall great appreciation and satisfaction with the proposed rehabilitative environment.…”
Section: Virtual and Extended Environments For Pwmsmentioning
confidence: 99%
“…Costeffective and easy to set up, they can provide useful settings for occupational therapy (Corrêa et al, 2013;Pruszyńska et al, 2022;Tada et al, 2022). An example is the immersive virtual kitchen game proposed by Pau et al (2023a) where the environment provides several activities of daily living tasks (e.g., tidying up, cooking, washing the dishes, etc.). Questionnaires conducted on an 8-week study on PwMS showed overall great appreciation and satisfaction with the proposed rehabilitative environment.…”
Section: Virtual and Extended Environments For Pwmsmentioning
confidence: 99%